Positively Aware? Conflicting Expert Reviews and Demand for Medical Treatment - Jorge Balat; Nicholas W. Papageorge; Shaiza Qayyum (Institute of Labor Economics (IZA), 2017)
We study the impact of expert reviews on the demand for HIV treatments. A novel feature of our study is that we observe two reviews for each HIV drug and focus attention on consumer responses when experts disagree. Reviews are provided by both a doctor and an activist in the HIV lifestyle magazine Positively Aware, which we merge with detailed panel data on HIV-positive men's treatment consumption and health outcomes. To establish a causal relationship between reviews and demand, we exploit the arrival of new drugs over time, which provides arguably random variation in reviews of existing drugs. We find that when doctors and activists agree, more positive reviews increase demand for HIV drugs. However, doctors and activists frequently disagree, most often over treatments that are effective, but have harsh side effects, in which case they are given low ratings by the activist, but not by the doctor. In such cases, relatively healthy consumers favor drugs with higher activist reviews, thus defying the doctor, which is consistent with a distaste for side effects. This pattern reverses for individuals who are in worse health and thus face stronger incentives to choose more effective medication despite side effects. Findings suggest that consumers demand information from experts according to the trade-offs they face when making health investments in the presence of adverse treatment side effects.
Keywords: I12; L15; M3; D12; D83; 330; health; information; product reviews; pharmaceutical demand; HIV/AIDS